Analysis Of Students' Ability In Solving Story Problems On FPB And KPK Material In Grade VII-B Of SMP Negeri 2 Sentani In The 2025/2026 Academic Year - Ismail, Mirna Wati; Kho, Ronaldo; Panjaitan, Agnes Teresa; Napitulu, Bettisari; Kulimbang, Elieser (JUPE : Jurnal Pendidikan Mandala, 2026)
This research is descriptive research using qualitative approaches. The purpose of this study is to analyze and describe students’ ability in solving word problems on the topics of Greatest Common Divisor (GCD) and Least Common Multiple (LCM) in relation to their learning outcomes (high, medium, and low) in Class VII-B of SMP Negeri 2 Sentani in the Academic Year 2025/2026. The students’ problem-solving abilities were examined through the following stages: (1) the ability to understand and identify the information in the problem; (2) the ability to plan the solution; (3) the ability to perform calculations correctly; and (4) the ability to answer the question or write the conclusion. The subjects of this study consisted of three students representing different levels of learning achievement: high, medium, and low. The data were collected through written tests and interviews. The written test consisted of three essay questions. The results of the study revealed that: (1) students with high learning outcomes were able to solve word problems effectively at all stages, including understanding and identifying information, planning solutions, performing calculations, and drawing accurate conclusions; (2) students with medium learning outcomes were able to understand the problem and plan solutions but made mistakes in the calculation and conclusion stages due to incorrect application of the LCM concept; and (3) Students with low learning outcomes were only able to understand the information in the problem but were unable to continue to the planning, calculation, or conclusion stages correctly due to the error in choosing the correct solution strategy, which was the confusion betweenthe use of the GCD (Greatest Common Divisor) and LCM (Least Common Multiple) concepts.